Problems of the Legitimacy of Biological Fathers as Guardians of Marriages of Children Born Out of Wedlock - Pornomo, Wahyu Adi; Arpangi, Arpangi (Jurnal Hukum Khaira Ummah, 2025)
Abstract. The problem of the status of children born out of wedlock creates legal complexity, especially related to marriage guardianship and lineage in Islam and positive Indonesian law. Children born out of wedlock often face the consequences of their parents' negligence, especially when girls need a marriage guardian for the validity of the marriage. Islamic Law and the Compilation of Islamic Law (KHI) Article 19 emphasizes marriage guardianship as a mandatory pillar, where the father has the main position as a lineage guardian. However, recognition of the biological father is often difficult to obtain if the parents' marriage is invalid, causing the illegitimate child to only be related to the mother according to the KHI. The MUI fatwa also confirms this. On the other hand, Constitutional Court Decision No. 46/PUU-VIII/2010 has opened up space for recognizing the civil relationship of illegitimate children with biological fathers through scientific evidence (DNA), regardless of lineage ties, creating tension between sharia norms and constitutional protection of children's rights. This study uses a normative juridical legal approach with a descriptive research type, utilizing library research to analyze secondary data. The primary legal materials used include the 1945 Constitution, the Criminal Code, the Criminal Procedure Code, the Marriage Law, and the KHI, supported by secondary legal materials such as relevant books and journals. The data collection method was carried out through literature studies, observations, and interviews with competent informants using purposive sampling. Data analysis was carried out qualitatively with a deductive-inductive thinking framework. The study found that the KHI explicitly cuts off the lineage of children resulting from adultery with biological fathers, appointing a judge as a marriage guardian. However, the Constitutional Court Decision and modern legal philosophy emphasize the protection of children's rights, justice, equality, and welfare, encouraging the recognition of biological fathers as marriage guardians under certain conditions if legally proven, in line with the views of the Hanafi school. However, in current Indonesian judicial practice, a judge remains the main solution for girls born from adultery without a valid marriage to guarantee the validity of the marriage.